Care for patients with suicidal behavior: perception of health professionals - Paula Mariane Langaro; Diego de Carvalho; Elcio Luiz Bonamigo (O Mundo da Saúde, 2022)
The growing number of suicide attempts in Brazil and in the world raises the need for qualified health professionals to provide this type of care and to report occurrences. This study aimed to describe the perception and preparation of professionals in a Health Region caring for patients with suicidal behavior. This was a descriptive, cross-sectional, quantitative study. Data were obtained through the application of a questionnaire given to health professionals who work in the public network belonging to the 15 municipalities of the 7th Health Region of the State of Paraná. For data analysis, Pearson's Chi-squared test was used. In general terms, health professionals did not feel prepared to treat patients with suicidal behavior. Most did not have sufficient education or training, were unaware of the risk stratification in mental health in accordance with APSUS notebook 8, and did not know how to insert these patients into the mental health network. In conclusion, there is a need for better preparation of health professionals to care for patients with suicidal behavior by strengthening continuing health education, from an intersectoral and interdisciplinary perspective, which is a measure that will also contribute to the improvement of notifications to the Ministry of Health.